Effects of Diet Formulation and Supplementation of an Algoclay Complex-Based Feed Additive in Grow-Finish Diets on Pig Growth Performance and Carcass Characteristics - L. Del Tuffo; J. C. Woodworth; S. S. Dritz; M. D. Tokach; J. M. DeRouchey; R. D. Goodband (Kansas Agricultural Experiment Station Research Reports, 2019)
The objective of this study was to evaluate the effect of feeding an algoclay complex- based feed additive (ACC, Olmix Group, Brehan, France) on growth performance and carcass characteristics of finishing pigs fed two different diet formulation regimens. A total of 1,188 pigs (PIC; 337 × 1050; initially 111.6 lb) were used in a 90-d study. Pens were blocked by initial weight and randomly assigned to diets with 11 pens per treatment and 27 pigs per pen. Dietary treatments were arranged in a 2 × 2 factorial with main effects of ACC addition (none or 0.1% until 220 lb and 0.05% thereafter) and diet formulation regimen (High vs. Low). The High diets were formulated to maximize growth performance and contained 3% added fat with no dried distillers grains with solubles (DDGS). The second feeding regimen (Low) included diets formulated with 70 kcal per lb less net energy, contained 30% DDGS, no added fat, and were formulated 0.10% below the standardized ileal digestible lysine requirement based on the same SID Lys:NE ratio used in the High diets. For overall performance, there were no interactions observed between diet formulation and added ACC for growth performance criteria, carcass data, or economics. From d 56 to 90, pigs fed the ACC diets had increased (P<0.001) average daily gain (ADG) and improved (P= 0.016) feed efficiency (F/G) compared with the control fed pigs. Overall, ADG was greater (P= 0.027) for pigs fed ACC diets compared with those fed diets without ACC. Overall, pigs fed High diets had improved growth performance and heavier weights than pigs fed Low diets. For carcass characteristics, pigs fed High diets tended to have greater (P= 0.062) loin depth and greater (P<0.001) carcass weight than pigs fed Low diets. No evidence for differences was observed for carcass characteristics between the control and the ACC fed pigs. For economic analysis, pigs fed High diets had increased feed cost and feed cost per lb gain, but also had greater revenue and income over feed cost (IOFC). No evidence for differences (P>0.05) were observed for feed cost, feed cost per lb of gain, revenue, or IOFC between pigs fed diets with or without ACC. In conclusion, the addition of ACC to finishing diets showed an improvement in growth performance but no differences were observed in the economic analysis. Feeding the High dietary regimen increased feed costs per pig, but the improvements in growth performance offset the added cost and improved IOFC compared with those pigs fed the Low diets.
Keywords: algoclay complex; feeding regimen; finishing pigs